The other-race effect in perception and recognition: Insights from the complete composite task. - Ruth Horry (Journal of Experimental Psychology: Human Perception and Performance, 2015)
People are more accurate at recognizing faces of their own race than faces from other races, a phenomenon known as the other-race effect. Other-race effects have also been reported in some perceptual tasks. Across three experiments, White and Chinese participants completed recognition tests as well as the complete paradigm of the composite task, which measures participants’ abilities to selectively attend to the target region of a face while ignoring the task-irrelevant region of the face. Each task was completed with both own- and other-race faces. At a group level, participants showed significant own-race effects in recognition, but not in the composite task. At an individual difference level, the results provided no support for the hypothesis that a deficit in holistic processing for other-race faces drives the other-race effect in recognition. We therefore conclude that the other-race effect in recognition is not driven by the processes that underpin the composite effect.